The potential use of e-procurement in the Malaysian palm oil industry supply chain - Kamarulzaman, Nitty Hirawaty; Eglese, Richard W. (Universiti Putra Malaysia Press, 2013)
E-procurement is electronic methods of conducting business transactions particularly purchasing activities. Many companies around the world have started to apply the technologies though there are still some which refuse to utilize them. The objective of this paper was to investigate the application of e-procurement technologies in managing purchasing activities among the Malaysian Palm Oil Industry (MPOI) supply chain players. Responses from the representative player of each stage of the MPOI supply chain were gathered via in-depth interviews using an open ended questionnaire. A detailed analysis based on content analysis from the responses revealed that e-procurement technologies could be a potential tool to increase the efficiency of purchasing activities, enhance purchasing and searching processes, as well as providing relevant information on materials, and aid in the reduction of human error. Certain products for example fresh fruit bunch (FFB), crude palm oil (CPO), crude palm kernel oil (CPKO) and palm kernel however were found to be impractical to use e-procurement tools due to several reasons. These products were commonly supplied by very established suppliers who are quite conventional in their business. Thus e-procurement tools are not often used in their purchasing activities. This paper concluded that e-procurement technologies were not 'really' available in the MPOI supply chain.